2016
DOI: 10.1037/neu0000257
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the consequences of impaired monitoring of learned behavior in attention-deficit/hyperactivity disorder using a Bayesian hierarchical model of choice response time.

Abstract: Objective Performance monitoring deficits have been proposed as a cognitive marker involved in the development of Attention Deficit Hyperactivity disorder (ADHD), but it is unclear whether these deficits cause impairment when established action sequences conflict with environmental demands. The current study applies a novel data-analytic technique to a well-established sequence learning paradigm to investigate reactions to disruption of learned behavior in ADHD. Method Children (ages 8–12) with and without A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 114 publications
1
28
0
Order By: Relevance
“…Arguably one of the best ways to incorporate accuracy and speed of performance into a single set of indices is through a computational approach known as diffusion modelling (Ratcliff & McKoon, 2008). This approach, which has long been used in the cognitive sciences and cognitive neurosciences, has recently begun to be adopted in the developmental (Cohen-Gilbert et al, 2014; Ratcliff, Love, Thompson, & Opfer, 2012), aging (Ratcliff, Thapar, & McKoon, 2004, 2011; Starns & Ratcliff, 2010), and clinical (Huang-Pollock et al, 2016; Huang-Pollock, Karalunas, Tam, & Moore, 2012; Karalunas, Huang-Pollock, & Nigg, 2012; Moustafa et al, 2015; Weigard, Huang-Pollock, & Brown, 2016; Weigard & Huang-Pollock, 2014; Wiecki, Poland, & Frank, 2015) literatures.…”
Section: Discussionmentioning
confidence: 99%
“…Arguably one of the best ways to incorporate accuracy and speed of performance into a single set of indices is through a computational approach known as diffusion modelling (Ratcliff & McKoon, 2008). This approach, which has long been used in the cognitive sciences and cognitive neurosciences, has recently begun to be adopted in the developmental (Cohen-Gilbert et al, 2014; Ratcliff, Love, Thompson, & Opfer, 2012), aging (Ratcliff, Thapar, & McKoon, 2004, 2011; Starns & Ratcliff, 2010), and clinical (Huang-Pollock et al, 2016; Huang-Pollock, Karalunas, Tam, & Moore, 2012; Karalunas, Huang-Pollock, & Nigg, 2012; Moustafa et al, 2015; Weigard, Huang-Pollock, & Brown, 2016; Weigard & Huang-Pollock, 2014; Wiecki, Poland, & Frank, 2015) literatures.…”
Section: Discussionmentioning
confidence: 99%
“…Prehn-Kristensen et al (2011) concluded that the processes underlying procedural sequence learning may differ between ADHD and TD. Despite these findings, other studies have suggested that procedural sequence learning is unaffected in ADHD (Vloet et al, 2010;Laasonen et al, 2014;Weigard et al, 2016;Pedersen and Ohrmann, 2018). Specifically, these studies have reported comparable reductions in response times across sequences blocks on variations of the SRT task in children and adults with ADHD and TD.…”
Section: Procedural Sequence Learning In Adhdmentioning
confidence: 88%
“…To date, only a handful of studies have explored procedural sequence learning in ADHD. Most of these studies have used the serial reaction time (SRT) task (e.g., Karatekin et al, 2009;Vloet et al, 2010;Prehn-Kristensen et al, 2011;Laasonen et al, 2014;Weigard et al, 2016;Pedersen and Ohrmann, 2018), which is a button-press task commonly used to measure implicit visualmotor sequence learning (Nissen and Bullemer, 1987;Howard and Howard, 1997). For this task, a visual stimulus appears in one of four horizontally-arranged squares on a screen.…”
Section: Procedural Sequence Learning In Adhdmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests EEA has some generality in influencing performance across multiple psychological domains. Third, EEA has been observed to be diminished in several psychiatric disorders 16,24,25 , though most studies thus far have examined attentiondeficit/hyperactivity disorder (ADHD) [26][27][28][29] , and different tasks were used across these studies, making comparisons across disorders difficult.…”
Section: Figure 1: the Diffusion Decision Model (Ddm)mentioning
confidence: 99%